History of the Development of Nagham Al-Qur'an in Indonesia - Suarni, Suarni; Syukrinur, Syukrinur (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Nagham is an art form of reciting the Quran. The application of art in reciting the Quran is highly dependent on the rules of Tajweed. Reciting the Quran according to Tajweed rules is a command found in the Quran and Hadith. By reciting the Quran by the rules of recitation, a beautiful sound melody called